2010
DOI: 10.5551/jat.3368
|View full text |Cite
|
Sign up to set email alerts
|

C-C Chemokine Receptor 2 Inhibitor Improves Diet-Induced Development of Insulin Resistance and Hepatic Steatosis in Mice

Abstract: Aim: Adipose tissue inflammation induced by macrophage infiltration through the MCP-1/CCR2 pathway is considered to play a pivotal role in the development of visceral obesity and insulin resistance. In the present study, therefore, we examined whether pharmacological inhibition of CCR2 is effective against the development of diet-induced metabolic disorders. Methods: C57BL/6 mice were fed a high fat and sucrose diet with or without propagermanium (CCR2 inhibitor, 5 or 50 mg/kg BW/day) for 12 weeks from 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
60
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 40 publications
10
60
0
1
Order By: Relevance
“…Of note, MCP-1 knockout mice also showed a trend towards lower hepatic steatosis and triglyceride deposition after 4 weeks of an MCD diet, but differences from WT mice did not reach significance in this short-term model 11. Our observation of reduced hepatic steatosis progression upon liver injury by mNOX-E36 administration is also in agreement with studies in which mice were fed a high fat diet; here, MCP-1 deficiency or CCR2 blocking also ameliorated hepatic steatosis and triglyceride content 35 36. In these studies, pro-inflammatory cytokines released by macrophages into the liver but also into other compartments such as adipose tissue were identified as crucial inducers of hepatic steatosis 35 36.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, MCP-1 knockout mice also showed a trend towards lower hepatic steatosis and triglyceride deposition after 4 weeks of an MCD diet, but differences from WT mice did not reach significance in this short-term model 11. Our observation of reduced hepatic steatosis progression upon liver injury by mNOX-E36 administration is also in agreement with studies in which mice were fed a high fat diet; here, MCP-1 deficiency or CCR2 blocking also ameliorated hepatic steatosis and triglyceride content 35 36. In these studies, pro-inflammatory cytokines released by macrophages into the liver but also into other compartments such as adipose tissue were identified as crucial inducers of hepatic steatosis 35 36.…”
Section: Discussionsupporting
confidence: 89%
“…This is suggested to result from the suppression of recruitment of Ly6C-positive monocytes, Kupffer cells, and HSCs by CCR2 inhibition. Although we did not find M2 polarization in CCR2 Ϫ/Ϫ macrophages, it has been reported that a CCR2 inhibitor can shift M1 type macrophages to M2 phenotypes (35). This further suggests that the CCR2 inhibitor, not only suppresses the recruitment of macrophages and HSCs, Ϫ/Ϫ , TLR9 Ϫ/Ϫ , and MyD88 Ϫ/Ϫ mice.…”
Section: And Myd88mentioning
confidence: 39%
“…68 On the other hand, genetic deletion of the CCR2 receptor was found to attenuate obesity and recruitment of macrophages to the AT, 69 in agreement with findings obtained with pharmacological antagonists of CCR2. 69,70 Moreover, in obese AT, expression of genes characteristic of M2-polarized macrophages is reduced, while inflammatory, Ly6C hi , M1-polarized macrophages predominate, and this phenotypic switch in AT macrophages is reduced in mice lacking CCR2. 71 Collectively, these studies indicate that interfering solely with CCL2 or CCR2 is probably not sufficient to antagonize the complex metabolic alterations that accompany obesity and that beneficial effects on insulin resistance may be at least partially independent of AT inflammation.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 98%